PENGGUNAAN METODE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATERI IMAN KEPADA RASUL SISWA KELAS IV SD NEGERI 2 BABADAN KEC. NGAJUM - Khasanah, Uswatun; Sulalah, Sulalah; Arifa, Laily Nur (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This research is based on the issue of how the use of the "make a match" method can improve students' learning outcomes in the subject of belief in the prophets in the fourth-grade class at SD Negeri 2 Babadan, Ngajum District. The objective of this research is to describe the use of the "make a match" method in improving students' learning outcomes in Islamic Religious Education (PAI) on the subject of belief in the prophets at SD Negeri 2 Babadan, Ngajum District. This research employs a classroom action research with two cycles. Each cycle consists of 4 stages: planning, action, observation, and reflection. The target of this research is fourth-grade students. The data obtained include learning outcomes and observation sheets of teaching and learning activities. The analysis results indicate that students' learning outcomes have improved from Cycle I to Cycle II. In the pre-cycle, 17% of students completed the material, in Cycle I, 50% of students completed the material, and in Cycle II, 100% of students completed the material above the Minimum Mastery Criteria (KKM). The conclusion of this research is that the use of the "make a match" method can improve students' learning outcomes. Abstrak Penelitian ini berdasarkan permasalahan Bagaimanakah penggunaan metode make a match dalam meningkatkan hasil belajar siswa pada materi iman kepada rasul kelas IV SD Negeri 2 Babadan Kec.Ngajum. Sedangkan tujuan dari penelitian ini adalah Untuk mendeskripsikan penggunaan metode make a match dalam meningkatkan hasil belajar siswa pada mata pelajaran PAI materi iman kepada rasul di SD Negeri 2 Babadan Kec. Ngajum. Penelitian ini menggunakan penelitian tindakan kelas sebanyak dua siklus. Setiap siklus terdiri dari 4 tahap yaitu, perencanaan, tindakan, observasi, dan refleksi. Sasaran penelitian ini adalah siswa kelas IV. Data yang diperoleh berupa hasil belajar, lembar observasi kegiatan belajar mengajar. Dari hasil analis didapatkan bahwa hasil belajar siswa mengalami peningkatan dari siklus I sampai siklus II yakni, pra-siklus 17% siswa tuntas, siklus I 50% siswa tuntas dan siklus II 100% siswa tuntas diatas KKM. Simpulan dari penelitian ini penggunaan metode make a match dapat meningkatkan hasil belajar siswa.